Integration of Ultrathin Metasurfaces with a Lens for Efficient Polarization Division Multiplexing. Issue 12 (29th March 2019) - Cong, Xuan; Zhang, Lei; Li, Jiaqi; Zhang, Min; Su, Hong; Li, Irene Ling; Ruan, Shuangchen; Liang, Huawei
Abstract: Integration of an ultrathin (≈0.08 λ), flexible bilayer metasurface with a conventional lens is proposed to independently control two orthogonally polarized waves. By judiciously selecting the building blocks of the metasurfaces, several control functionalities are demonstrated such as generating Bessel beams and off‐axis and on‐axis focusing for the cross‐polarized THz waves generated in the polarization conversion resonance. Simultaneously, the lens focuses the copolarized waves normally. Then, THz polarization division multiplexing is achieved, and the total control efficiency is as high as 72–88% in the experiment. Furthermore, the proposed metasurface is fabricated via a cost‐effective standard flexible printed circuit technique, which shows high potential for integration with other functional devices. It is believed that the strategy to integrate metasurfaces with conventional elements will greatly enrich the family of THz functional devices. Abstract : Polarization division multiplexing at 0.14 THz (one of the atmospheric windows of the THz wave), which is quite challenging for a metasurface or a bulk functional device alone, is theoretically and experimentally realized by integrating an ultrathin, flexible bilayer metasurface with a conventional lens. This method may open a novel path for THz integration technology.